Infectious keratitis in leprosy. Issue 2 (1st February 1999) - John, Deepa; Daniel, Ebenezer
Abstract : AIM: To describe leprosy characteristics, ocular features, and type of organisms that produce infective corneal ulcers in leprosy patients. METHOD: The records of all leprosy patients admitted for treatment of corneal ulcers between 1992 and 1997 were reviewed. RESULTS: 63 leprosy patients, 53 males and 10 females, are described. 16 were tuberculoid and 47 lepromatous. 25 patients had completed multidrug therapy. 10 patients had face patches, eight had type I reaction, and 10 had type II reaction. 43 (68%) patients had hand deformities. In 54% of patients pain was absent as a presenting symptom. 19 patients gave a history of trauma. In 15 patients ulcers had also occurred on the other eye, five of them having occurred during the study period and the rest before 1992. Of the 68 eyes with corneal ulcers, 28 had madarosis, 34 had lagophthalmos, nine had ectropion, three had trichiasis, six had blocked nasolacrimal ducts, and 39 decreased corneal sensation. In 14 eyes, a previous lagophthalmos surgery had been done. 16 patients were blind at presentation. 32% of ulcers were located centrally. After treatment only 18% of the eyes showed visual improvement. Five types of fungus were cultured, two of them rare ocular pathogens. CONCLUSIONS: Corneal ulcers occur more in males and in the lepromatous group of patients. Decreased corneal sensation, lagophthalmos and hand deformity are closely associated. Indigenous treatment and late presentations were notable in many patients. Visual outcome is not good. There is increased risk of developing an ulcer in the other eye. Fungal corneal ulcers are not uncommon.